2021
DOI: 10.1016/s2665-9913(21)00151-x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune inflammatory rheumatic diseases and COVID-19 outcomes in South Korea: a nationwide cohort study

Abstract: Background Real-world evidence on the association between autoimmune inflammatory rheumatic diseases, therapies related to these diseases, and COVID-19 outcomes are inconsistent. We aimed to investigate the potential association between autoimmune inflammatory rheumatic diseases and COVID-19 early in the COVID-19 pandemic. Methods We did an exposure-driven, propensity score-matched study using a South Korean nationwide cohort linked to general health examination records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 38 publications
(44 reference statements)
6
79
1
1
Order By: Relevance
“…Despite our first report [14] with relatively small sample size (n = 10), we found a favorable outcome in this large prospective cohort of BS patients. Our current observations are also in contrast with a number of studies who reported increased risk for severe COVID-19 infection and COVID-19 related death among patients with RD [4,26,27]. In our study, while 18.7% had lung involvement, none of the patients died or had a thrombotic event.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Despite our first report [14] with relatively small sample size (n = 10), we found a favorable outcome in this large prospective cohort of BS patients. Our current observations are also in contrast with a number of studies who reported increased risk for severe COVID-19 infection and COVID-19 related death among patients with RD [4,26,27]. In our study, while 18.7% had lung involvement, none of the patients died or had a thrombotic event.…”
Section: Discussioncontrasting
confidence: 99%
“…A meta-analysis of seven case-controlled studies demonstrated that the risk of COVID-19 in AD was significantly higher than in control patients (OR 2.19, 95% CI 1.05-4.58%, p = 0.038) [26]. Similarly, a nation-wide study from South Korea recently reported that patients with inflammatory arthritis had an increased risk of testing positive for SARS-CoV-2 (OR 1.20, 95% CI 1.03-1.40%; p = 0.020) compared to those without inflammatory arthritis [27]. Finally, the high incidence rate of COVID-19 in the BS cohort may be due to the ascertainment bias as we mentioned earlier.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, patients with inflammatory arthritis showed an increased likelihood of testing positive for COVID-19 and severe COVID-19 outcomes inconsistent with our study. 32 However, that study involved some differences in the inclusion criteria and the definition of severe COVID-19. The researchers included RA as an inflammatory arthritis with other types of arthritis such as psoriatic arthritis and compared patients with and without inflammatory arthritis; in contrast, we only included patients with RA.…”
Section: Discussionmentioning
confidence: 99%
“…This COVID-19 cohort study is a retrospective, nationwide case-control study using Korean National Health Insurance Service COVID database (NHIS-COVID DB) that includes all Koreans who were tested for SARS-CoV-2 through services facilitated by Korean National Health Insurance Service (NHIS), Korea Centers for Disease Control and Prevention, and the Health Insurance, Review & Assessment Service of Korea between January 1, 2020 and June 4, 2020 as a result of medical or Korea Centers for Disease Control referral. From this data, we obtained the demographic information, previous health screening results, three years of complete healthcare records, test results for SARS-CoV-2, and clinical outcomes of COVID-19 from January 1, 2015 to August 18, 2020 [ 8 ]. The detailed study protocol used was previously described [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%